Sex hormones and their relationship with leptin and cardiovascular risk factors in pre and post-menopausal Nigerian women with metabolic syndrome (2015)
Metabolic Syndrome (MS), which affects 33.1% of Nigerians, predisposing them to cardiovascular disease (CVD) risk, has been associated with the female gender. The cardioprotective effect of oestradiol against CVD is now controversial and was investigated in premenopausal with MS (PRMMS) and postmenopausal women with MS (POMMS). A total of 191 women (44 PRMMS, 126 POMMS and 21 premenopausal women without MS (PRM) (controls) with mean (s.d) age of 40.0 (6.9), 57.0 (8.8), 29.0 (6.8) years were participants of this study. Demography, blood pressure (BP), anthropometry, hormones, fasting plasma glucose (FPG) and lipids were obtained by standard methods. Data were significant at (P<.05). Age, parity, all anthropometric measures, FPG, leptin, ET ratio and FSH were significantly higher while HDLC, testosterone and prolactin were significantly lower in PRMMS compared with controls (P<.03). In comparison of POMMS with PRMMS, age, parity, WHR, systolic BP, TG, FSH and LH were significantly higher while body weight, HC, and leptin were lower in POMMS compared with PRMMS (P<.05). DBP positively predicted oestradiol in PRM only (P=.044) while oestradiol positively predicted testosterone in PRMMS only (P<.001). In POMMS only, DBP positively predicted testosterone; testosterone, ET ratio and FSH positively predicted oestradiol while LDLC and oestradiol positively predicted the ET ratio (P<.03). Metabolic syndrome may predispose both pre and postmenopausal women to the risk cardiovascular disease and type 2 diabetes mellitus. Oestradiol may protect against cardiovascular diseases in women without metabolic syndrome only.